The behaviour of sheep around natural waterways and their impact on water quality : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Animal Science at Massey University, Palmerston North, Manawatu, New Zealand - Bunyaga, Aloyce Shukran (Massey University, 2026)
The impacts of extensively managed sheep on the natural environment have received little attention in comparison to beef and dairy cattle in New Zealand. In particular, there is a paucity of information on the interaction of sheep with natural waterways and their impact on water quality. Access of livestock, such as cattle, to waterways has been shown to be a cause of poor water quality due to pugging damage and excretion entering the waterway. In New Zealand, regulations require that cattle, deer, and pigs are excluded from waterways, but there are no such requirements for sheep. The aims of this thesis were to: 1) examine the behaviour of sheep on a hill country paddock, which was transected by a natural waterway during winter, spring and summer, 2) investigate whether drinking water restriction influenced the behaviour of sheep, 3) determine the impact of sheep on the water quality of the waterway across seasons and, 4) investigate the influence of slope and aspect on the spatial distribution of sheep across three seasons. Observations of behaviour showed that sheep spent little time near the natural waterway compared to other areas within the paddock across seasons. However, study ewes showed a spatial preference for flat to low sloped areas of the paddock while utilising south and north facing slopes more than the rest of the aspect categories. Sheep preferred using culverts to cross the waterway than to try cross it via other means. In addition, the degree of interaction of sheep with the waterway was not influenced by the availability of reticulated water from a trough. Overall, ewes had minimal interaction with the waterway and therefore, had little impact on the water quality. This may have been due to the high moisture content of pasture; thus, meaning the sheep were not physiologically required to interact with the waterway to drink. Results from this study have contributed to the knowledge of sheep behaviour around natural waterways. These results are crucial for informing future decision making related to the management of sheep in and around riparian zones, for example, potential impacts of sheep on waterways could be reduced through the strategic placement of culverts, water sources and other paddock features on areas preferred to be utilised by sheep such as lowlands areas, near crossings and those with green pasture. The results are also crucial to informing future government policy focused on stock exclusion of sheep from waterways and suggest the current New Zealand stock exclusion policy which does not include sheep is appropriate.
Keywords: ewes; behaviour; waterway; water quality; Sheep; Behavior; Climatic factors; Grazing; Environmental aspects; Riparian areas; Water quality; New Zealand